Case Report: Further Delineation of Neurological Symptoms in Young Children Caused by Compound Heterozygous Mutation in the PIEZO2 Gene - Klaniewska, Magdalena; Jedrzejowska, Maria; Rydzanicz, Malgorzata; Paprocka, Justyna; Biela, Mateusz; Wolanska, Ewelina; Pollak, Agnieszka; Debek, Emilia; Sasiadek, Maria; Ploski, Rafal; Gos, Monika; Smigiel, Robert (Frontiers in Genetics, 2021)
The recessive PIEZO2 associated with distal arthrogryposis with impaired proprioception and touch (DAIPT), is characterized by generalized hypotonia, perinatal respiratory distress, significantly delayed psychomotor development and progressive symptoms of scoliosis and distal arthrogryposis. PIEZO2 protein is a unique ion channel that converts mechanical impulses into cellular signals in somatosensory neurons and is involved in various mechanotransduction pathways. The senses of touch and proprioception rely on the ability to detect and transduce mechanical force. The molecular and neural mechanisms underlying these sensory functions still remain poorly defined. The cases described so far concerned older children, teenagers and young adults, whereas our patients with compound heterozygous variants in the PIEZO2 gene identified in exome sequencing showed first symptoms at birth (hypotonia, joint contractures). Moreover, among the cases described by us there is the youngest diagnosed child to date.